Overlapping Surgery for Ankle Fractures: Is It Safe?. Issue 8 (August 2020) - Baessler, Aaron; Mullis, Brian; Loder, Randall; Corn, Karsen; Mavros, Charles
Abstract : Objective: To determine whether the practice of overlapping surgery influenced patient safety after open reduction internal fixation (ORIF) for ankle fractures. Design: Retrospective case–control. Setting: Level 1 Academic Midwest trauma center. Patients: All patients who underwent ankle fracture ORIF by a single surgeon were eligible for our study, with 478 total patients. Intervention: Cases that were overlapping were compared against cases that were not overlapping. Cases were defined as overlapping if there was greater than 30 minutes of overlap between procedural times. Patient complications were recorded up to a year from the index surgery. Main Outcome Measure: Unexpected return to surgery. Results: There were 478 ankle fracture ORIF patients, 238 with at least 3 months follow-up; 124 (52%) in the overlapping group and 114 (48%) in the nonoverlapping group. There was no difference in the rate of unexpected return to surgery ( P = 0.76), infection ( P = 0.52), readmission ( P = 0.96), painful implant ( P = 0.62), malunion ( P = 0.27), nonunion ( P = 0.52), or arthritis ( P = 0.39) between the overlapping and nonoverlapping groups. There were 467 isolated ankle fractures used for time analysis. Average procedure time was 26 minutes longer for the overlapping group than the nonoverlapping group ( P < 0.01). Conclusions: Overlapping surgery causes increased operative time for ankle ORIF, but there was no apparent increased risk to the patients for short-term complications. The need for graduated resident responsibility required by ACGME guidelines need to be weighed against the decreased efficiency of operating room time. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.